Ginsenoside Rh2 in combination with IFNγ potentiated the anti-cancer effect by enhancing interferon signaling response in colorectal cancer cells - Huang Mu-yang; Xu Chun-cao; Chen Qian; Zhang Yan-ming; Lyu Wen-yu; Ye Zi-han; Li Ting; Huang Ming-qing; Lu Jin-jian (Acta Pharmacologica Sinica, 2025)
Interferon gamma (IFNγ) can amplify immune cell-mediated anti-tumor immunity, as well as directly kill cancer cells. Ginsenoside Rh2 (Rh2), a bioactive compound in traditional Chinese medicine, exhibits anti-cancer effects such as inhibiting proliferation and metastasis. Our earlier research found that Rh2 combined with IFNγ enhanced CXCL10 secretion in cancer cells. Here, we explored whether Rh2 and IFNγ exerted more potent anti-cancer activity in vitro and in vivo, along with its mechanisms and clinical value. Our data showed that Rh2 in combination with IFNγ resulted in a remarkably increased cytotoxicity in colorectal cancer cells including HT29, LoVo and T84 cell lines. Consistently, intratumoral injection with Rh2 plus IFNγ further restricted the HT29 tumor growth in vivo, and importantly, it was demonstrated to be safe for mice. Meanwhile, the combo treatment activated the stimulator of interferon genes (STING) pathway in cancer cells, promoting the transcription of downstream type I interferon. RNA sequencing revealed a dramatically transcriptional alteration in cancer cells with combo treatment and indicated that Rh2 further augmented the activation of interferon signaling pathway, compared with the IFNγ alone. Inhibition of janus kinase (JAK) by ruxolitinib could significantly rescue the cell death-triggered by the combo treatment. Then, a gene set named Rh2+IFNγ signature genes (RISG) was defined, which contained top 20 significantly upregulated genes from the combo treatment. Patients who exhibited a favorable response to the immunotherapy had a higher expression of RISG in tumor compared with those who did not respond. And the high expression of RISG was correlated with better clinical outcome in patients with colorectal cancer (CRC) and skin cutaneous melanoma (SKCM). Herein, the combination of Rh2 with IFNγ served as a promising strategy for cancer treatment, and its-derived RISG gene set also exhibited potential value in predicting clinical outcome.